Cashless society trend: A bibliometric analysis and Islamic economic research opportunities - Rabbani, Faiq Shidqi; Herman, Sebastian (Journal of Islamic Economics Lariba, 2024)
Introduction Rapid technological developments, especially in the banking sector, such as digital or non-cash payments, have encouraged people to switch from traditional cash transactions to non-cash transactions. This behavioral change has become a trend in a cashless society. Objectives This study aims to analyze the behavior of a cashless society based on publications indexed in the Scopus database. Method This study utilizes bibliometric analysis using R Biblioshiny to collect and analyze literature related to cashless society and Sharia principles. Results The results show a significant increase in publications related to the cashless society since 2015 until 2023. Additionally, the most analyzed documents include articles, conference papers, and books. Batiz Lazo B is the most cited and influential author and frequently used keywords include cashless society, economics, Malaysia, payment methods, technology adoption, digital payment, and others. Implications The study highlights the importance of the shift towards non-cash transactions, which offer significant benefits, underscoring the need for further research and development in the future. Originality/Novelty This research contributes to the recent literature on cashless society and its relations with Sharia-compliant practices in Muslim society.